Neglected tropical diseases activities in Africa in the COVID-19 era: the need for a "hybrid" approach in COVID-endemic times - David Molyneux; Simon Bush; Ron Bannerman; Philip Downs; Joy Shu'aibu; Pelagie Boko-Collins; Ioasia Radvan; Leah Wohlgemuth; Chris Boyton (BMC, 2021)
Abstract With the coronavirus disease 2019 (COVID-19) pandemic showing no signs of abating, resuming neglected tropical disease (NTD) activities, particularly mass drug administration (MDA), is vital. Failure to resume activities will not only enhance the risk of NTD transmission, but will fail to leverage behaviour change messaging on the importance of hand and face washing and improved sanitation-a common strategy for several NTDs that also reduces the risk of COVID-19 spread. This so-called "hybrid approach" will demonstrate best practices for mitigating the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by incorporating physical distancing, use of masks, and frequent hand-washing in the delivery of medicines to endemic communities and support action against the transmission of the virus through water, sanitation and hygiene interventions promoted by NTD programmes. Unless MDA and morbidity management activities resume, achievement of NTD targets as projected in the WHO/NTD Roadmap (2021-2030) will be deferred, the aspirational goal of NTD programmes to enhance universal health coverage jeopardised and the call to 'leave no one behind' a hollow one. We outline what implementing this hybrid approach, which aims to strengthen health systems, and facilitate integration and cross-sector collaboration, can achieve based on work undertaken in several African countries.